PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA APARAT PEMERINTAH DAERAH DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL PEMODERASI Studi pada Pemerintah Daerah Kabupaten Temanggung - Arin Sulistyaningsih; Rohmad Yuliantoro (Universitas Ahmad Dahlan, 2015)
This research is aimed to examine the effect of budget arragement participation, organization culture and leadership style toward local goverment officials performance, with organization commitment as moderating variable on local government of Temanggung. Budget is an effective short tem arrangement, high scale of budget arragement participation,organization culture and leadership style toward local goverment officials performance, and organization commitmen can support budget run well. Populations in this research are local government officials in SKPD Temanggung. Object in this research are head of division, division head, sub-division head and section head, data collection methode in this research with survei and questionaire. Data analysis technique used in this research are double linier regression and moderated regression analysis. The results of this research show that budget arrangement participation and leadership style influence the local government performance, organization commitment can moderate organization culture effect and leadership style toward local government performance, but it can not moderate budget arrangement participation effect toward local government officials performance.